Biochemical and physiological responses of sugarcane cultivars to soil water deficiencies - Rafaela Josemara Barbosa Queiroz; Durvalina Maria Mathias dos Santos; Antonio Sergio Ferraudo; Samira Domingues Carlin; Marcelo de Almeida Silva (Scientia Agricola, 2011)
For sugarcane (Saccharum spp.) crops, the effects of an environmental stress, especially water deficiency, may cause severe productivity reduction, inferring negatively in the sugarcane industry. The tolerance of two sugarcane cultivars to a lack of water was made by analyzing the levels of the osmoprotectors, trehalose and free proline, and the biometrical variables of their initial growth. Biochemical and physiological responses of the cultivars, when subjected to water stress, were assayed to determine how these plants tolerate drought. The study was conducted in an acclimatized greenhouse (29.7 ± 4.3ºC and 75.0 ± 10.1% relative humidity) during 100 days and was divided into random blocks using a factorial 2 × 3 × 2 design (sugarcane cultivars × water availability × time periods) with four replicates. Forty days after germination, sugarcane was planted in pots (12 dm³) containing topsoil material taken from a medium textured Rhodic Ferralsol, submitted to three levels of water availability (WAS): 55% (control), 40% (moderate stress) and 25% (severe stress), for 60 days. The effect of the WAS on the accumulation of trehalose and free proline was detected in both cultivars, although it was found to be more distinctive for the cv. IAC91-5155. Trehalose and free proline are biochemical and physiological indicators of water deficiency. The cv. IAC91-5155 had altered growth and allocation of biomass when subjected to severe water stress conditions. The univariate and the multivariate analysis of the biochemical and physiological responses, presented by the IAC91-5155 cultivar, indicate relative tolerance to drought conditions.